(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2021)
This article presents the measurement of the Multidimensional Poverty Index in undergraduate students of the Universidad Centroccidental Lisandro Alvarado. This public education institution is located in western Venezuela, in the state of Lara and is made up of seven deans that host twentythree training programs. The study is based on data collected during 2018, through the "Survey of living conditions of university students of the Universidad Centroccidental Lisandro Alvarado" at two different times. The methodology used was that of Alkire and Foster (2008) and adapting to dimensions that affect the student population such as: food, health, transportation, security and economic conditions. The study presents a total incidence rate, in which there is a fourfold increase in just seven months. In the incidence rate by dimensions, it is exposed that the highest affectation is related to basic needs (food, health and economy). In general, multidimensional poverty increased widely in the same year. This situation is explained in a context of impoverishment and crisis that rapidly affects multiple aspects of human life and is classified by international organizations as a Complex Humanitarian Emergency.